ANALISIS PERBANDINGAN PENGARUH LANGSUNG DAN TAK LANGSUNG FAKTOR BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KINERJA KARYAWAN PADA UPTD PARKIR - Lilis Ardini (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
This study  examines  the role of service variable to commitment variable as intervening variable. Respondents of this study are 87 samples by using purposive sampling method. Questionnaire consists of 3 variables, those are organizational culture with 26 indicators, then commitment with 15 indicators, and managerial work  with 10 indicators . The result of this study shows that managerial work  may have direct influence to commitment  and have indirect influence that is from organizational culture to commitment as a new intervening to managerial work. Direct influence of organizational culture  to managerial work  that is  is 0,232. Indirect influence of organizational culture  to commitment  that is 0,810, meanwhile from commitment to managerial work, that is 0,617. Therefore, indirect influence, that (0,810)*(0,617)=0,4997. Hypothesis stating that assumption of organization culture effects the performance higher than organization culture in UPTD Surabaya Parking are refused. Organization culture that effects employee performance is. 0,49977; while organization culture effects on employee’s performance is  0,232. This result may provide a conducive company, then, emerge employee commitment. Based on those results, it can be suggested that a company should give more emphasize to organizational culture  and commitment  because there is evidence that it may cause customer’s managerial work because organizational culture is a very important factor in guaranteeing UPTD  Public Parking DISHUB Surabaya.